2020
DOI: 10.1111/all.14323
|View full text |Cite
|
Sign up to set email alerts
|

The effect of air pollutants on airway innate immune cells in patients with asthma

Abstract: Isolation of cDNA encoding a newly identified major allergenic protein of rye-grass pollen: Intracellular targeting to the amyloplast .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Kim et al correlated measurements of air pollutants around patients’ houses, including particulate matter (PM), with asthma status and with the frequency of innate immune cells (ILC) in induced sputum. A significant positive correlation between the amount of PM with a diameter ≤10 µm and asthma control was reported accompanied by an increased frequency of ILC2s in induced sputum 6 …”
Section: Environmental Risk Factors For the Development Of Asthmamentioning
confidence: 93%
See 2 more Smart Citations
“…Kim et al correlated measurements of air pollutants around patients’ houses, including particulate matter (PM), with asthma status and with the frequency of innate immune cells (ILC) in induced sputum. A significant positive correlation between the amount of PM with a diameter ≤10 µm and asthma control was reported accompanied by an increased frequency of ILC2s in induced sputum 6 …”
Section: Environmental Risk Factors For the Development Of Asthmamentioning
confidence: 93%
“…1,2 In addition, environmental factors, genetic polymorphisms, and epigenetic factors contribute to the development of asthma, heterogeneity in phenotyping, and steroid responsiveness. [3][4][5][6] Environmental interventions and exposure control can improve asthma control and exacerbations. 7 The incidence and prevalence of asthma are increasing, though regular use of inhaled corticosteroids (ICS) reduces mortality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 ILC2 are more sensitive to outdoor pollution-driven proliferation than other ILC types. 10 ILC2s are deemed as steroid resistant, however, other asthma treatments might decrease their pro-inflammatory capacity. 11 An in vivo model showed that tiotropium attenuated ILC2dependent airway inflammation by suppressing IL-4 production from basophils.…”
Section: Innate Immunitymentioning
confidence: 99%
“…]10 μm and asthma control was reported accompanied by an increased frequency of ILC2s in induced sputum. 6 Recently Yang et al showed prenatal exposure to PM with an aerodynamic diameter of smaller than 10 μm (PM) has a higher association with airway hyperresponsiveness (AHR) and the risk of a new diagnosis of asthma at an early school age than current and lifetime exposure. Therefore, stricter monitoring and avoidance of exposure to PM might considerably reduce the onset of future asthma development in schoolchildren.…”
Section: Environmental Risk Factors For the Development Of Asthmamentioning
confidence: 99%